Towards a further understanding of cement hydration in the presence of triethanolamine - Lu, Zichen; Kong, Xiangming; Jansen, Daniel; Zhang, Chaoyang; Wang, Jian; Pang, Xiaofan; Yin, Jianhao (Cement and Concrete Research, 2020)
The acting mechanism of triethanolamine (TEA) on cement hydration was studied by combination of techniques including calorimetry, in-situ XRD and pore solution analysis. Results show that, a high dosage of TEA (0.5%) results in accelerated aluminate reaction and retarded silicate reaction during hydration of ordinary Portland cement (OPC). The initial dissolutions of C3S, C3A, C4AF and gypsum are greatly facilitated by TEA. The secondary fast reactions of C4AF and C3A triggered by the earlier sulfate-depletion produce a new exothermic peak before the main hydration peak of C3S that usually presents as a shoulder after the main hydration peak in the reference sample. TEA retards the hydration of pure C3S, but much more severely delays the silicate reaction in OPC system, attributed to the negative interference of aluminate reaction on silicate reaction. The new insights into the interaction between TEA and OPC contribute to the theoretical base for regulating cement hydration.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Cement hydration; Complexation; Triethanolamine (TEA)